Financing of Private Hydropower Projects - Head, Chris (Washington, DC: World Bank, 2013)
This study provides an overview of the issues and challenges related to the private financing of hydropower projects in developing countries. From the very limited pool of projects that have already reached or are nearing financial closure, ten have been chosen for the study from five countries with the most active in promoting private hydro development. Collectively the case study projects provide a reasonable cross-section of private hydro schemes that have been or are being developed. The financing of greenfield private infrastructure on a limited-recourse basis in developing countries faces certain common issues irrespective of the type of project. However, hydropower faces additional difficulties caused by the site-specific nature of projects, high construction risk and long construction periods, their capital-intensive nature with a high proportion of local costs, unpredictable output subject to river flows and broader water management constraints, complex concession process to achieve transparency in the award and pricing of output, and environmental sensitivities. The study suggests the need for longer-term financing to better suit hydropower characteristics, a regulatory framework and realistic public-private risk-sharing arrangements responsive to the requirements of hydropower projects, and the careful preparation of projects by the public sector to enable their formulation on an adequate technical and contractual basis for development as a private concession.